Antioxidant and Antidiabetic Compounds from Ebony Leaf Extract (Diospyros celebica Bakh.) and Their Correlation with Total Phenolic and Flavonoid Compounds in Various Solvent Extraction - Apriandini, Lisya; Hanafi, Muhammad; Djamil, Ratna; Desmiaty, Yesi; Narrij Lotulung, Puspa Dewi; Artanti, Nina (Journal of Natural Product for Degenerative Diseases, 2023)
Ebony (Diospyros celebica. Bakh) is a native plant of Indonesia that is used as a traditional medicine for diabetes mellitus. Previous studies state that ethanol extract from ebony leaves significantly reduced blood glucose levels of diabetic rats induced by alloxan. This ability is thought to be caused by secondary metabolites which is phenolic and flavonoid compound. However, research related to structure compounds in extract and composition of solvent variations in the extraction process to get the most optimal activity and also their correlation with total phenolic and flavonoid compounds has not been carried out. This study aimed to evaluate the composition of the optimum solvent in the extraction process and also to know the structure compounds contained in the extract. In the present study, we extracted the ebony leaves with three solvents of different polarity (ethanol-water), i.e. ethanol 50% (EtOH), EtOH 70%, and EtOH 96%. Quantitative estimation of total phenolic and flavonoid contents. These extracts were future evaluated for their activity and the content of compounds in the extract was identified using LCMS/MS. The results showed that phenolic compounds that have been identified in ebony leaf extract are methyl gallate and (-)-Epiafzelechin 3-gallate and we found there were significant differences in all test parameters between the three extracts which is EtOH 96% extract gave the best.